2021
DOI: 10.1186/s13033-021-00445-3
|View full text |Cite
|
Sign up to set email alerts
|

The mental health impact of COVID-19 outbreak: a Nationwide Survey in Iran

Abstract: Background Disease outbreak not only carries the risk of death to the public due to the infection, but it also can lead to unbearable psychological impact on the mental health of the individuals. This study aims to explore and evaluate the burden of psychological problems on the Iranian general population during the outbreak of COVID-19. Method A cross-sectional web-based survey was conducted among the general population of Iran age 15 and above. D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 39 publications
(23 reference statements)
2
56
2
1
Order By: Relevance
“…Our results suggest that men had better knowledge, while women had better attitudes and practicing behavior against the COVID-19. Similar results have also been reported in Iran, Pakistan, and Saudi Arabia ( 7 , 15 , 30 ). The reason behind this high knowledge among the men compared to women could be attributed to: (a) more easy access to print electronic, and SM updates about the severity of the pandemic by the men compared with women; (b) men have more habits of reading newspapers or listening news compared with women and in accordance with the reported literature ( 31 ); (c) tea shops in Pakistan are also considered a great place for the men to spend a lot of time in discussing various social issues, and (d) most of the men visit the mosques five times a day to offer their prayers and find time to share social news as well.…”
Section: Discussionsupporting
confidence: 89%
“…Our results suggest that men had better knowledge, while women had better attitudes and practicing behavior against the COVID-19. Similar results have also been reported in Iran, Pakistan, and Saudi Arabia ( 7 , 15 , 30 ). The reason behind this high knowledge among the men compared to women could be attributed to: (a) more easy access to print electronic, and SM updates about the severity of the pandemic by the men compared with women; (b) men have more habits of reading newspapers or listening news compared with women and in accordance with the reported literature ( 31 ); (c) tea shops in Pakistan are also considered a great place for the men to spend a lot of time in discussing various social issues, and (d) most of the men visit the mosques five times a day to offer their prayers and find time to share social news as well.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, PHQ-9 and GAD-7 were used and the prevalence was less compared to studies that used other questionnaires like DASS ( Sediri et al, 2020 ). Other studies using PHQ-9 and GAD-7 had yielded comparable results ( Cuelemans et al, 2021 ; Shahriarirad et al, 2021 ). All the studies mentioned above were conducted online, either using convenience sampling or snowball sampling.…”
Section: Discussionmentioning
confidence: 62%
“…Studies done in general population have evaluated psychological problems in women separately. One such study found the prevalence of depressive and anxiety symptoms in women to be 16.9 % and 22.1 %, respectively, higher than that in men ( Shahriarirad et al, 2021 ); while an Indian study, done in the initial two weeks following the onset of lockdown, observed depressive symptoms in 22.8 %, anxiety symptoms in 20.5 % and stress in 12.3 % of the women ( Verma and Mishra, 2020 ). Thus, depressive and anxiety symptoms as well as stress were found to vary widely in different studies from different geographical areas and at different time periods in relation to lockdown.…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, COVID-19 which was declared a pandemic and global emergency by the WHO on 11th March 2020 has seized the attention of medical staff, governments, and people and affected other disease management and diagnosis approaches. Among the group at risk are children, with the disease affecting them in various ways [ 4 6 ]. There is a growing global concern that SARS-CoV-2-related inflammatory syndrome is emerging in children.…”
Section: Discussionmentioning
confidence: 99%